The Impact of Enterprises' Shadow Banking Activities on Business Performance: A Test Based on Mediator Effect of Investment Scale and Investment Efficiency. Issue 14 (14th November 2019) - Han, Xun; Hus, Sara; Li, Jianjun
ABSTRACT: In recent years, China's financial sector has gradually been alienated from the real sector, allowing financial innovation and regulatory arbitrage add their own value to finance. High interest rates in the financial industry have led to changes in the real sector, revealing a trend toward "financialization" and "quasi-financialization"; a typical example of this includes nonfinancial enterprises' shadow banking activities. In this article, we use annual data from 2004 to 2015 of A share listed companies on the Shanghai and Shenzhen Stock Exchanges, to examine the influence of nonfinancial enterprises' shadow banking activities on business performance. The results show that, overall, enterprises' shadow banking activity improve operating performance. In addition, from the perspective of earning structure, nonfinancial enterprises' shadow banking business increases financial benefits, but has a significantly negative effect on operating income. Further tests show that enterprises engaged in shadow banking activities will impact operating income through the two intermediary variables of investment scale and investment efficiency. However, the negative effect of investment in crowding out operating income is greater than that of the efficiency-improving effect on operating income. This article provides policy guidance in terms of recognizing diverse aspects of shadow banking system that divorce the real economy from the financial economy.